Public works inspectors' manual - Birch, Silas B. (BNi Building News, 2008)
A complete operational technical guidebook for professionals charged with the responsibilities of inspecting all types of public works construction for city, county, state and federal agencies. This comprehensive Manual has become the standard reference for public works professionals across the nation for over 50 years. It clearly spells out, in-step-by-step detail, testing procedures and inspection guidelines for virtually every type of work and material - from asphalt and aggregates, to pipe and prestressed concrete. --